Designing a system of learning materials to explain climate change to children - Lucy Blackwell (Problemy Wczesnej Edukacji)
Our climate is changing faster than anticipated, creating an urgent responsibility for educators to prepare children for global warming and help them understand what is happening and how everything is interconnected. Inspired by the Montessori method, this project explores the process of designing a set of learning materials to teach children (aged 6 to 9) about climate change. These materials were tested in a Montessori school and a state primary school over 5 weeks, using a qualitative research methodology of observation and semi-structured interviews. A cross-curricula approach, grounded in systems thinking, proved to be an effective way to break down and organize the content for this topic. A variety of different types of learning materials were designed including: card matching, experiments, listening to sounds, collaborative drawing, and engaging with physical materials. The hands-on learning materials that directly reflected their purpose, proved to be the most effective in achieving the learning outcomes. A consideration of how the design process followed many of the Montessori principles is explored, whilst also identifying a need to be more flexible with the Montessori approach and use the method as a springboard for new ideas.